2015
DOI: 10.5267/j.msl.2015.5.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of private investment, exports, imports, inflation and GDP on per capita premium: Evidence from members of OPEC countries

Abstract: In this study, we examine the relationship between GDP, export, import, private sector investment and inflation on insurance per capita of OPEC countries. Insurance is a non-banking institution that by making sure and secure, can make and develop manufacturing and service rendering easier. Insurance companies can make financial steady and reduce stress. So, it plays essential role in economy. For this aim, data over the period 2003-2011 is collected. We use regression and SPSS software for analysis. Results fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, as time passes, the risk rises as more countries join the fray. Past research by Abedini and Darabi (2015) Table 1: and Balcilar et al (2020) suggested that the presentation of the traded flow of goods reduces the marginal productivity of firms related to risk premium and is driven by a positive or negative joint reaction of domestic firms' performance and households' consumption to foreign shocks. Investors are afforded robust risk mitigation thanks to the policy environment's emphasis on minimal risk performance across globalization, political institutions, and financial liberalization.…”
Section: Resultsmentioning
confidence: 99%
“…However, as time passes, the risk rises as more countries join the fray. Past research by Abedini and Darabi (2015) Table 1: and Balcilar et al (2020) suggested that the presentation of the traded flow of goods reduces the marginal productivity of firms related to risk premium and is driven by a positive or negative joint reaction of domestic firms' performance and households' consumption to foreign shocks. Investors are afforded robust risk mitigation thanks to the policy environment's emphasis on minimal risk performance across globalization, political institutions, and financial liberalization.…”
Section: Resultsmentioning
confidence: 99%
“…Export is among the most important activities for development of economies (Abedini & Darabi, 2015;Ghasemi et al, 2015). Farooqui (2016) investigated the bilateral trade and economic growth between China and India and emphasized that export would be the biggest concern in development of India's economy.…”
Section: Introductionmentioning
confidence: 99%